Interactive macroeconomics: A pluralist simulator - Franz J. Prante; Alessandro Barmucci; Eckhard Hein; Achim Truger (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
The aim of our contribution is to present an innovative instrument to teach macroeconomics at the undergraduate and master level. We develop a digital learning platform to present and explore some controversies at the very foundations of macroeconomic theory. For this purpose, we explicitly present two competing paradigms, the new-Keynesian and the post-Keynesian one. Several interactive scenarios are made available where the user can take control over different economic policy instruments and is guided through a set of problems that require appropriate actions in the context of the different approaches.
Keywords: A22; A23; E12; E17; E60; 330; macroeconomics teaching; simulations; pluralism; new Keynesian macroeconomics; post-Keynesian macroeconomics